2017
DOI: 10.1016/j.diii.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MR imaging-targeted biopsies of the prostate in biopsy-naïve patients. A single centre study

Abstract: Detection rate of prostate cancer did not show significant differences between a TB and a SB technique in biopsy-naïve patients. However, targeted prostate biopsies demonstrated a better sampling effectiveness thus reducing the cores needed to diagnose clinically significant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…Many groups reported mpMRI had excellent negative predictive value for ruling out csPCa [10] . Yet, analysis of several prospective monocenter trials showed that combined systematic and targeted biopsy performed substantially better than targeted biopsy alone [52] , [56] , [57] , [58] , [59] , which is in line with the MRI-FIRST results. Interestingly, one retrospective study of 211 patients with unilateral MRI lesions reported that systematic biopsy was useful in addition to targeted biopsy in the lobe containing the MRI lesion; in contrast, the added value of the systematic biopsy of the contralateral lobe was marginal [60] .…”
Section: The Role Of Mpmri In the Management Of Clinically Localized supporting
confidence: 70%
See 1 more Smart Citation
“…Many groups reported mpMRI had excellent negative predictive value for ruling out csPCa [10] . Yet, analysis of several prospective monocenter trials showed that combined systematic and targeted biopsy performed substantially better than targeted biopsy alone [52] , [56] , [57] , [58] , [59] , which is in line with the MRI-FIRST results. Interestingly, one retrospective study of 211 patients with unilateral MRI lesions reported that systematic biopsy was useful in addition to targeted biopsy in the lobe containing the MRI lesion; in contrast, the added value of the systematic biopsy of the contralateral lobe was marginal [60] .…”
Section: The Role Of Mpmri In the Management Of Clinically Localized supporting
confidence: 70%
“…In biopsy-naïve patients, several prospective monocenter trials gave conflicting results on the added value of targeted biopsy as compared to standard systematic biopsy [48] , [49] , [50] , [51] , [52] . However, three recent large prospective multicenter studies gave concordant results that may change guidelines on this matter.…”
Section: The Role Of Mpmri In the Management Of Clinically Localized mentioning
confidence: 99%
“…We found 39 retrospective studies, 46 prospective studies, and 13 RCTs where periprocedural antibiotics were administered [12] , [13] , [14] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [67] , [68] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , …”
Section: Evidence Synthesisunclassified
“…Local anaesthetic transperineal procedures were relatively well tolerated, with a low rate of procedural abandonment (26/ 6954, 0.37%; Table 2). Of the 14 studies that assessed pain during different stages of the biopsy, LA infiltration was rated as the most uncomfortable stage in 13 studies, while ultrasonography probe insertion was rated most uncomfortable in one study by Thurtle et al [7,8,14,23,25,26,29,30,32,34,38,39,41,42].…”
Section: Tolerabilitymentioning
confidence: 99%
“…For example, the high rate of positive biopsies in some studies using the PPTAS device is likely to have been influenced by patient selection, as only patients with mpMRI Prostate Imaging-Reporting and Data System (PI-RADS) scores 3-5 and Likert scores 3-5 were included [25,36]. Additionally, clinically significant cancer was defined as Gleason ≥3 + 4 in all studies, however, Bass et al and Garcia Bennet et al also included cancer core length ≥4 mm as clinically significant cancer [6,23]. This variation in the definition of clinically significant cancer is a further example of the disparity in prostate biopsy and reflects the heterogeneity of the included studies.…”
Section: Cancer Detectionmentioning
confidence: 99%